Correction: Rhodium-catalysed selective C–C bond activation and borylation of cyclopropanes. Issue 10 (3rd March 2021) - Wang, Yandong; Bai, Jingyi; Yang, Youqing; Zhao, Wenxuan; Liang, Yong; Wang, Di; Zhao, Yue; Shi, Zhuangzhi
Abstract : Correction for 'Rhodium-catalysed selective C–C bond activation and borylation of cyclopropanes' by Yandong Wang et al., Chem. Sci., 2021, DOI: ; 10.1039/d0sc06186g .